The application of updating PIM-Taiwan criteria in clinic-visiting older patients with polypharmacy. (December 2018) - Chang, Chirn-Bin; Lai, Hsiu-Yun; Hwang, Shinn-Jang; Yang, Shu-Yu; Wu, Ru-Shu; Liu, Hsing-Cheng; Chan, Ding-Cheng
Background: PIM-Taiwan criteria were first established in 2010 for potentially inappropriate medications (PIMs). Currently, updating of PIM criteria is mandatory because of newly established evidence and newly developed medications. This study aims to evaluate the prevalence of PIM based on country-specific PIM criteria and factors associated with PIM use by applying 2010 version and newly updating PIM-Taiwan criteria in a cohort with polypharmacy. Methods: The baseline data of Medication Safety Review Clinic Taiwan (MSRC–Taiwan) study were used to investigate the prevalence of PIMs. Older patients (aged ⩾65 years) who were either having polypharmacy or visited ⩾3 different physicians were enrolled between August and October 2007. Bivariate analysis and multivariate logistic regressions were used to evaluate the factors associated with PIM use. Results: The prevalence of having at least one PIM was 46.1% for 2010 version and increased to 74.6% for 2018 version. The average number of PIMs generally to be avoided per patient also increased for 2018 version (0.2 versus 1.2, p < 0.0001). In contrast, the average number of PIMs considering chronic conditions per patient decreased (0.6 versus 0.3, p < 0.001). The associated chronic conditions of PIM users were distinct between 2010 and 2018 version. The major leading PIMs were benzodiazepines (BZDs) in both versions of criteria. Conclusions: As there were significant differences in medication lists between PIM-Taiwan version 2010 and 2018, the prevalence of PIM and factors associated with PIM users varied accordingly. Physicians should pay special attention before prescribing BZDs which keep being the major leading PIM.